Intradermal Electroporation of Naked Replicon RNA Elicits Strong Immune Responses - Johansson, Daniel X.; Ljungberg, Karl; Kakoulidou, Maria; Liljeström, Peter (PLOS ONE, 2012)
RNA-based vaccines represent an interesting immunization modality, but suffer from poor stability and a lack of efficient and clinically feasible delivery technologies. This study evaluates the immunogenic potential of naked in vitro transcribed Semliki Forest virus replicon RNA (RREP) delivered intradermally in combination with electroporation. Replicon-immunized mice showed a strong cellular and humoral response, contrary to mice immunized with regular mRNA. RREP-elicited induction of interferon-γ secreting CD8+ T cells and antibody responses were significantly increased by electroporation. CD8+ T cell responses remained substantial five weeks post vaccination, and antigen-specific CD8+ T cells with phenotypic characteristics of both effector and central memory cells were identified. The immune response during the contraction phase was further increased by a booster immunization, and the proportion of effector memory cells increased significantly. These results demonstrate that naked RREP delivered via intradermal electroporation constitute an immunogenic, safe and attractive alternative immunization strategy to DNA-based vaccines.